Proceedings of IEEE International Symposium on Information Theory
DOI: 10.1109/isit.1997.613388
|View full text |Cite
|
Sign up to set email alerts
|

A characterization of binary bent functions

Abstract: A recent paper by Carlet introduces a general class of binary bent functions on (GF(2)) n (n even) whose elements are expressed by means of characteristic functions (indicators) of (nÂ2)-dimensional vector-subspaces of (GF(2))

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 4 publications
0
13
0
3
Order By: Relevance
“…Carlet [2] introduced the generalized partial spreads class (G P S) of bent functions and conjectured that any bent function belongs to G P S. This conjecture was proved in affirmative by Carlet and Guillot [3]. A similar construction which provides a unique representation of bent functions was proposed by Carlet and Guillot [4].…”
Section: Theorem 9 Let Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Carlet [2] introduced the generalized partial spreads class (G P S) of bent functions and conjectured that any bent function belongs to G P S. This conjecture was proved in affirmative by Carlet and Guillot [3]. A similar construction which provides a unique representation of bent functions was proposed by Carlet and Guillot [4].…”
Section: Theorem 9 Let Nmentioning
confidence: 99%
“…Taking any such bent set of cardinality ≥ 4, say 3 , which satisfy the conditions of Theorem 19(a), because S is a bent set closed under addition.…”
Section: Case (Ii)mentioning
confidence: 99%
“…Qu et al [41] have found, by computer enumeration, an interesting class of bent functions with 6 variables. Carlet and Guillot [19], Dobbertin [25], Kumar et al [29], and Langevin [42] have analyzed some bent function constructions, characterizations, properties, and generalizations. Tokareva [34] introduces lower bound on the number of bent functions that can be obtained by the iterative constructions proposed by Canteaut and Charpin [43].…”
Section: Introductionmentioning
confidence: 99%
“…From the preceding discussion, such a word satisfies We note that Wada [30] has also recently recognised the connection between bent functions and PAPR reduction in MC-CDMA. Bent functions have received a good deal of attention, see for example [1], [4], [5], [8], [28], [29], [33], and a brief overview can be found in [17, Chap. 14, Sec.…”
Section: A Walsh-hadamard Transforms and Bent Functionsmentioning
confidence: 99%